Thwarting Sybil Attack by CAM Method in WSN using Cooja Simulator Framework - Singhal, Prateek; Sharma, Puneet; Rizvi, Sheenu (International Journal of Engineering and Technology, 2018)
In the area of IoT Sybil attack is vulnerable where the fake identities can manipulate or misuse pseudoidentities to negotiate the successof spam and Internet of Things. The nodes illegitimately claim multiple identities against sensor and Ad-Hoc networks. The hostile or faulty remote computing elements faces the security thread on large- scale peer-to-peer systems. We have a trust agency to certify the identities prevent from the â€œSybil Attackâ€. Multiple identities that control sustainable fraction of systems so prevent from loss of information while data exchanging via networks or internet.In this paper the proposed CAM (Comparing and Matching) approach to prevent from Sybil attack by verifying the position of the sensors or node with their location ID. We match the ID of the node while data exchanging over network. We specifically given a complete assure security for WSN that these kinds of attack come out with unicast as well as multicast. We have practically analysis the simulation of network by gagingthe end-to-end delay, pack delivery and throughput of packets under the numerous circumstances to compute the effectiveness of packets. This simulation is on the erudite tool that is Cooja under a Contiki OS and highlight the security over data exchanging and exemplify the use feature for intrusion detection â€œSybil Attackâ€ in the Internet of Things.Â Â
Keywords: IoT; WSN; Sybil attack; CAM; Position verification; Cooja.